PENERAPAN SERVICE LEARNING PADA ANAK ADHD (ATTENTION DEFICIT HIPERACTIVITY DISODER) (Studi kasus pada aspek Speed Delay dan Hiperactivity Di RA Insan Kamil Tumpang) - Kuswanti, Tanti (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
Inclusive of education as an educational service is general. The concept of implementing education is determined for regular children and children with special needs. In children with special needs, it focuses on children with ADHD who experience language delay disorders (speed delay) and hyperactive children. The purpose of the study was to describe the form of service learning services. The research method used in descriptive-qualitative research through data collection techniques using observation/field note data methods, interviews, and documentation. Data analysis conducted by examining based on gradual assessment indicators. The results of the study found based on Service learning collaborate the BCCT method as a learning concept in the classroom to hone child-oriented abilities based on aspects of center activities. The learning process that is prepared in a structured manner can obtain maximum results. The findings of the results were obtained through an evaluation process that emphasized that the BCCT method emphasizes learning that hones children's skills. In addition, cooperation with the medical sector is a form of school program that is carried out every six months. The conclusion of the research findings is that the design of child-oriented activities, the use of clear methods, and providing services for ADHD children that are medical in nature. This will help children's growth and development in terms of learning aspects at school and health aspects for students and it is very important for each institution to work together in the health sector to carry out institutional work programs effectively and efficiently.